Cutaneous presentation of disseminated histoplasmosis as a solitary peri‐anal ulcer. Case report and discussion. (6th April 2016) - Hong, Janet H.; Stetsenko, Galina Y.; Pottinger, Paul S.; George, Evan
Abstract : Disseminated histoplasmosis has a diverse and non‐specific range of clinical signs and symptoms. In a significant minority of patients, cutaneous lesions are apparent at the time of initial presentation, affording an opportunity to establish the diagnosis from a skin biopsy. The most frequently reported clinical scenario in immunocompromised patients with cutaneous involvement is that of multiple papulo‐nodular lesions on the face, trunk or extremities. The following report features an immunocompetent patient who presented with a solitary ulcerated plaque on the buttocks close to the anal verge. This case presentation underscores the broad spectrum of clinical presentations as well as the potential for diagnostic confusion with protozoa such as Leishmania or Trypanosoma species during histopathologic examination if special stains for fungal organisms are not performed.